2007
DOI: 10.1111/j.1365-2702.2007.01765.x
|View full text |Cite
|
Sign up to set email alerts
|

Validity of an instrument to measure the impact of valve heart disease on the patient's daily life

Abstract: The Heart Valve Disease Impact on daily life could be a useful instrument to measure the impact of heart valve disease and to evaluate the response to health interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
31
0
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(48 citation statements)
references
References 21 publications
8
31
0
9
Order By: Relevance
“…The fact that the domain, Adaptation to the disease, did not identify differences between groups was attributed to its composition, with only two non correlated items, as evidenced in other studies (7)(8) .…”
Section: Referencesmentioning
confidence: 58%
See 4 more Smart Citations
“…The fact that the domain, Adaptation to the disease, did not identify differences between groups was attributed to its composition, with only two non correlated items, as evidenced in other studies (7)(8) .…”
Section: Referencesmentioning
confidence: 58%
“…Lower scores mean that patient does not recognize the disease and treatment consequences in his life and, if they occur, they are not evaluated as bad. Although this instrument has been developed to evaluate beliefs of patients with valvular heart disease (7) , it was observed that the IDCV can also be used to evaluate the impact imposed by cardiac disease chronicity (7) . A previous study demonstrated its reliability and validity for assessment of the disease impact among patients with CAD (8) .…”
Section: Instrument To Measure the Impact Of Coronary Disease On Patimentioning
confidence: 99%
See 3 more Smart Citations